Buenas Prácticas de Almacenamiento de medicamentos en el Hospital Víctor Lazarte Echegaray, Trujillo-2017 - Pinillos Lujan, Alexandra Emperatriz (2019)
In this research work, the level of compliance with Good Medicine Storage Practices was determined in the Víctor Lazarte Echegaray Hospital, Trujillo-2017. o analyze the compliance of the indicators, the format of the Inspection Guide for Druggists, Specialized Stores and Customs Warehouses prepared by the General Directorate of Intake and Drug Drugs (DIGEMID) was used, which consists of 8 factors for its evaluation: Quality assurance, Personnel, Facilities, Equipment and Instruments, Warehouse, Documentation, Claims, Withdrawal from the market and Self-inspections. The results obtained a high level of compliance in the 8 factors: quality assurance system 100%, staff 87,5%, facilities, equipment and instruments 93,75%, warehouse 100%, documentation 80 %, claims 100%, withdrawal from the market 100% and self-inspections 80%.